2010
DOI: 10.1021/bi100741z
|View full text |Cite
|
Sign up to set email alerts
|

Functional Switching of Amphitrite ornata Dehaloperoxidase from O2-Binding Globin to Peroxidase Enzyme Facilitated by Halophenol Substrate and H2O2

Abstract: Amphitrite ornata dehaloperoxidase (DHP) is the first heme-containing globin possessing a native peroxidase enzymatic activity. DHP catalyzes the H(2)O(2)-dependent dehalogenation of halophenols. By possessing this detoxifying enzymatic activity, these organisms are able to thrive in an environment contaminated with toxic haloaromatics. It has been proposed that DHP evolved from a dioxygen carrier globin protein and therefore possesses dual physiological roles of O(2) carrier and dehaloperoxidase. Although DHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 22 publications
9
73
0
Order By: Relevance
“…On the basis of the results from this study for the activation of oxy-DHP as well as our previous findings, 25 shown in Scheme 2, we illustrate the mechanism for the H 2 O 2 -mediated oxidation of oxy-DHP to the ferric state in the presence of substrate TCP (as proposed previously 25 ) or ferrocyanide (newly found in this study). In the first phase, oxyferrous DHP is oxidized to ferric DHP by TCP • or ferricyanide (with bimolecular rate constant k 1 or k 1 app ), where k 1 or k 1 app denotes the rate constants for ferrous DHP in the absence or presence of O 2 , respectively (i.e., k 1 app is an O 2 concentration-dependent value).…”
Section: ■ Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the basis of the results from this study for the activation of oxy-DHP as well as our previous findings, 25 shown in Scheme 2, we illustrate the mechanism for the H 2 O 2 -mediated oxidation of oxy-DHP to the ferric state in the presence of substrate TCP (as proposed previously 25 ) or ferrocyanide (newly found in this study). In the first phase, oxyferrous DHP is oxidized to ferric DHP by TCP • or ferricyanide (with bimolecular rate constant k 1 or k 1 app ), where k 1 or k 1 app denotes the rate constants for ferrous DHP in the absence or presence of O 2 , respectively (i.e., k 1 app is an O 2 concentration-dependent value).…”
Section: ■ Discussionsupporting
confidence: 86%
“…MS detection was in the electron impact (EI) ionization mode, and a VG70S mass spectrometer scanning from 50 to 450 amu was used for product identification. 25 During the conversion, an absorption spectral change with a single set of isosbestic points (412, 528, and 592 nm) was observed, suggesting that no detectable intermediates are involved. To further probe the conversion mechanism, we have performed more detailed investigations of this study with an oxy-DHP:H 2 O 2 :substrate concentration ratio of 1:1:1.…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…Detailed studies have been performed regarding the oxidation of chlorophenols by lactoperoxidase [16], lignin peroxidase (LiP) [17], horseradish peroxidase (HRP) [18][19][20], dehaloperoxidase [21][22][23][24][25][26][27][28][29][30][31][32] and Caldariomyces fumago chloroperoxidase [33,34]. Among these peroxidases, HRP is an especially promising candidate for use as a bioremediation catalyst because of its (a) stability resulting in easier storage and handling, (b) ability to oxidize a large number of chlorophenols, (c) flexibility to function at wide ranges of temperature and pH, (d) and, most importantly, ready availability and relatively low cost [13,14,[35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic competency of Compound ES for oxidizing substrates has been demonstrated (22,32,36,37). In the absence of a reducing 2,4,6-trihalophenol co-substrate, the formation of a species termed Compound RH, which has not been found in any other globin, was observed (21,22,37).…”
mentioning
confidence: 96%
“…Yet DHP is itself distinct from other globins; it has little sequence homology with other hemoglobins, possesses a crystallographically characterized internal substrate binding site for 2,4,6-trihalophenols (16,17), and has been shown to utilize hydrogen peroxide to oxidize a range of substrates such as mono-, di-, and trisubstituted halophenols with bromine, chlorine, or fluorine as substituents (18,19). Moreover, the DHP peroxidase cycle can be initiated from both the ferric and ferrous (or oxyferrous) oxidation states (20,21). Thus, as a bifunctional globin-peroxidase capable of functioning from the reduced form, DHP may represent a new emerging class of peroxidases that shares neither sequence nor structural homology with any of the known peroxidases.…”
mentioning
confidence: 99%